The Implementation of Prophetic Education at Junior High School Level - Fauzi, Arif Ahmad; Kamilah, Adinda (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2020)
The current educational process is moving from a monotonous, indoctrinate, teacher-centered, top-down, mechanical, verbal, and cognitive process. However, there is an impression that the current practice of Islamic education is sterile from the context of the reality that it is unable to contribute to the various problems that occur. One of the educational problems in adolescents is reflected in the data from the social services. There are five of the eight cases handled by the social service for the protection of women and children are juvenile delinquency cases. Therefore, we need an interpretation and reorientation as well as a paradigm shift from current educational practices. As Muslims, we have the Messenger of Allah as a role model for education. The teaching prophetic techniques and methods can change generations and create a masterpiece in the form of khairu ummah. Among the principles of prophetic education is to strengthen faith before studying the Qur'an. Prophetic education also has a basis on which to become the foundation. The implementation of prophetic education itself consists of several processes, namely planning, organizing, implementing, and evaluating. This study aims to examine the entire process of implementing prophetic education at the secondary school level, especially in SMP Bina Insan Boarding School. The research method used is field research and library research. The data are then analyzed theoretically and philosophically for further conclusions.